Deep Brain Stimulation for Craniocervical Dystonia (Meige Syndrome): A Report of Four Patients and a Literature‐Based Analysis of Its Treatment Effects. Issue 8 (24th September 2015) - Wang, Xiu; Zhang, Chao; Wang, Yao; Liu, Chang; Zhao, Baotian; Zhang, Jian‐guo; Hu, Wenhan; Shao, Xiaoqiu; Zhang, Kai
Abstract : Objectives: The aim of this study was to report on four patients with craniocervical dystonia (CCD) treated with deep brain stimulation (DBS). In addition, we investigated the treatment efficacy and surgical outcome predictors by the review and analysis of previously published studies. Methods: Four patients with CCD underwent DBS of the globus pallidus internus (Gpi) or subthalamus nucleus (STN). PubMed and MEDLINE searches were performed to obtain detailed information on patients who underwent DBS for CCD. The primary efficacy endpoint was the change in the Burke–Fahn–Marsden Dystonia Rating Scale (movement and disability scores, BFMDRS‐M/D) after surgery. Results: Seventy‐five patients were included in the pooled analysis, including 69 patients with Gpi‐DBS and 6 patients with STN‐DBS. The mean follow‐up of time was 28.0 months after surgery. The mean BFMDRS‐M score was 24.5 ± 11.2 preoperatively and 8.1 ± 5.7 postoperatively at the final follow‐up evaluation, with a mean improvement of 66.9% ( p < 0.001). The mean BFMDRS‐D score was 8.1 ± 4.6 preoperatively and 3.6 ± 2.5 postoperatively, with a mean percentage improvement of 56.0% ( p < 0.01). Positive correlations were found between each of the preoperative movement and disability scores and percentage of postoperative improvement ( r = 0.247, p = 0.034; r = 0.331, p = 0.034, respectively). Conclusion: GPi/STN‐DBS is an effective treatment for patients with medically refractory CCD, including those with severe preoperative symptoms. The age at CCD onset and the disease duration do not predict improvement in movement scores.